Literature Overall of Fatigue Analysis Approaches of Vehicle Components Made of Rubber - Tomposné Szüle, Veronika (International Journal of Engineering and Management Sciences, 2020)
Generally, the most frequently used structural materials are metals which have high strength and stiffness. However, there are many cases when other important properties come to the front, as well as high deformation capacity with elastic behavior, high viscosity namely good damping effect. Due to its above mentioned properties, rubber is widely used in vehicle and automotive industry. Vehicle components made of rubber usually exhibit large deformations. Cyclic finite deformations generate temperature in hyperelastic materials. Furthermore it is necessary to take into consideration the effects of ambient temperature. The mechanical properties of rubber depend on temperature and temperature changes can accelerate chemical alteration processes which lead to the material deterioration and fatigue processes. Research on fatigue behavior and fatigue properties of rubber has a great significance for predicting fatigue life and improving durability of rubber products. There are several studies on the fatigue behavior of rubber-based materials, but there is less research in the fatigue life prediction considering the influence of temperature and temperature changes. First purpose of this paper is summarizing the influence of temperature and temperature changes on the fatigue behavior of rubber. The second purpose of this study is to provide an overview of the state of the art on the fatigue life prediction of rubber with primary focus on the different methods available for prediction of fatigue life under the influence of temperature and temperature changes.